Evaluation of Pattern of Hearing Loss Among Patients Attending ENT Department - Srilatha K (Asian Journal of Medical Research, 2021)
Background: The aim is to evaluate pattern of hearing loss among patients attending ENT department. Subjects and Methods: Seventy- four adult patients in age ranged 18- 58 years of either gender of hearing loss was recruited for the study. Pure tone audiometry was performed using Amplaid 309 clinical audiometer. Pattern of hearing loss and degree of hearing loss was recorded. Results: Out of 74 patients, males were 40 and females were 34. Pattern of hearing loss was sensorineural which comprised of measles in 2, meningitis in 1, consanguinity in 10, prenatal causes in 3, maternal in 1, enteric fever in 1, hypoxia in 2 and low birth weight in 1. Under conductive causes were CSOM in 12, Otitis Externa in 5, external bodies in 3, otosclerosis in 2, secretary otitis media in 7, Otomycosis in 2 and cerumen in 1 and there were mixed causes in 21 cases. Degree of hearing loss was mild in 30, moderate in 24, severe in 12 and profound in 8 cases. The difference was significant (P< 0.05). Conclusion: The most common cause of hearing loss was conductive hearing loss in which chronic suppurative otitis media was prevalent one and maximum patients had mild degree of hearing loss.